Inter-individual Relationships between Sympathetic Arterial Baroreflex Function and Cerebral Perfusion Control in Healthy Males - Witter, Trevor; Tzeng, Yu-Chieh; O'Donnell, Terry; Kusel, Jessica; Walker, Bridget; Berry, Mary; Taylor, Chloe E. (Frontiers in Neuroscience, 2017)
Maintenance of adequate cerebral perfusion during normal physiological challenges requires integration between cerebral blood flow (CBF) and systemic blood pressure control mechanisms. Previous studies have shown that cardiac baroreflex sensitivity (BRS) is inversely related to some measures of cerebral autoregulation. However, interactions between the sympathetic arterial baroreflex and cerebral perfusion control mechanisms have not been explored. To determine the nature and magnitude of these interactions we measured R-R interval, blood pressure, cerebral blood flow velocity and muscle sympathetic nerve activity (MSNA) in 11 healthy young males. Sympathetic BRS was estimated using modified Oxford method as the relationship between beat-to-beat diastolic blood pressure and MSNA. Integrated control of cerebral blood flow was quantified using transfer function analysis metrics derived during rest and Tieck’s autoregulatory index following bilateral thigh cuff deflation. Sympathetic BRS during modified Oxford trials was significantly related to autoregulatory index (r = 0.64, p = 0.03). Sympathetic BRS during spontaneous baseline was significantly related to transfer function gain (r = -0.74, p = 0.01). A more negative value for sympathetic BRS indicates more effective arterial baroreflex regulation, and a lower transfer function gain reflects greater cerebral autoregulation. Therefore, these findings indicate that males with attenuated CBF regulation have greater sympathetic BRS (and vice versa), consistent with compensatory interactions between blood pressure and cerebral perfusion control mechanisms.